ANALYSIS OF STUDENTS’ MATHEMATICAL PROBLEM SOLVING ABILITIES BASED ON POLYA’S STAGES IN MATHEMATICS LEARNING IN GRADE IV AT SD 25 BANDA ACEH - Atika, Maula; Hayati , Zikra; Herawati, Herawati; Ningsih, Yuni Setia; Daniah, Daniah (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
The low level of mathematical problem-solving ability among elementary school students remains a challenge in mathematics learning, particularly in students’ ability to plan strategies, carry out solution steps, and review their answers. This study aimed to describe and analyze students’ mathematical problem-solving abilities based on George Polya’s stages in mathematics learning for fourth-grade students at SD Negeri 25 Banda Aceh. This research employed a descriptive qualitative approach. The research subjects consisted of five students selected purposively. Data were collected through problem-solving tests and interviews, while data analysis included data reduction, data presentation, and conclusion drawing based on the indicators of each problem-solving stage, namely understanding the problem, planning the solution, carrying out the plan, and looking back. The results showed that, in general, students were able to understand the given problems, but they still experienced difficulties in planning and carrying out solution steps systematically. In addition, the looking back stage had not been carried out optimally by most students. Overall, students’ mathematical problem-solving ability was categorized as moderate. This category indicates that students were able to fulfill some of the problem-solving indicators, but had not demonstrated consistent and optimal performance across all stages. Specifically, two students were able to complete all stages, one student experienced difficulties at the planning and implementation stages, while the other two students experienced difficulties at the planning, implementation, and looking back stages. These findings indicate the need to strengthen the planning, implementation, and reflection stages in the learning process so that students’ mathematical problem-solving abilities can develop optimally. Keywords: Mathematical Problem-Solving Ability, Polya’s Stages, Mathematics Learning, Elementary School